Pengembangan Kompetensi Mahasiswa Melalui Kegiatan Workshop Memasuki Dunia Kerja Bagi Mahasiswa di Program Studi S1 Manajemen Universitas Cenderawasih - Kuddy, Aprianto La'lang; Wijaya, Iriando; Harju, Leon Mitra; Agustin, Sheilla Putri; Manalu, Palti Maretto Caesar; Insoraky, Wilhemina Arafusau; Payokwa, Musa K (Cenderabakti: Jurnal Pengabdian Kepada Masyarakat, 2025)
Higher education institutions are considered successful when they produce graduates equipped to compete effectively in the workforce. However, many graduates currently struggle to compete effectively in the job market. Competition in the job market has caused unemployment in Indonesia to increase every year. One of the causes for the increase in unemployment among higher education graduates is the lack of knowledge and competence of students in the job recruitment process. To address this issue, this study proposes outreach through workshops. These workshops aim to familiarize students with the job recruitment process, increasing their chances of securing employment. By utilizing materials from practitioners, the workshops are expected to enhance students' knowledge and skills, better equipping them for the competitive job market.